KEANEKARAGAMAN JENIS DAN KONDISI EKOSISTEM PADANG LAMUN DI PANTAI MENGIAT, NUSA DUA, BALI - Alya Namira; I Wayan Arthana; I Wayan Darya Kartika (Environmental Research Center (PPLH) of Udayana University, 2021)
This study aimed to determine the diversity, conditions, and diversity of seagrass at Mengiat Beach Bali. The study was conducted for 1 month, January-February 2021. The study was conducted at 3 observation stations using the 50 × 50 cm quadratic transect method. There were 7 types of seagrass, namely Cymodocea rotundata, Syringodium isoetifolium, Halodule pnifolia, Halodule uniinervis, Halophiila ovalis, Thalassodendron cilliatum, and Thalassia hempriichii. The density condition of the seagrass beds at stations I, II, and III was classified as a scale of 5 with the number of stands > 175 ind/m2. The species Cymodocea rotundata had the highest density, which was 904 ind/m2. The percentage of cover condition at station I in the good criteria of a rich / healthy condition witha seagrass cover value of 61.73%, while stations II and III were in the damaged category with less rich / unhealthy conditions with value at station II of 58.44. % and station III of 45.97%. There are 10 types of associated biota found namely Tripneustes gratilla, Etisus splendisus, Linckia laevigata, Atergatis floridus, Ophiothrix fragilis, Echinometra viridis, Echinometra mathei, Echinaster luzonicus, and Fromia Milleporella.